Effectiveness of high strength repair mortars in structural patch repairs of concrete members under axial compression - Naraghi, Vafa (Department of Civil Engineering, 2025)
There is a dearth of knowledge and research into the performance and efficacy of repair materials used in structural concrete patch repair applications. The repercussions of this have led to the development of repair standards and guidelines that fail to adequately cover requirements for structural repair, often poor repair material choice, and ultimately concrete repair failure. This research set out to determine the efficacy of high strength cement-based materials in structural patch repair of concrete elements under axial compression. This was determined with respect to the ability of the repair material to contribute to load sharing in the repaired element under service loads. Three commercially available high strength cement-based repair materials were tested for their strength, elastic modulus, shrinkage and creep properties. The tested repair material properties were then used as inputs into an analytical model to determine the distribution of stress in the repaired element over-time. The research has shown that the repair materials do not contribute to load sharing in the long term for patch repaired concrete elements under axial compression. Thus, ‘structural' repair materials and ‘structural' patch repairs are considered ineffective in the context of the simulations conducted in this research. The analytical model may be used to inform repair material choice as well as a basis for future research within the field of structural concrete patch repairs.